Korupsi Perspektif Hukum Islam: Upaya, Dampak dan Penanggulangan - Vandita, Lalu Yoga (Fakultas Syariah IAI Muhammadiyah Bima, 2025)
Corruption is a crucial problem that affects almost all countries in the world and is one of the main inhibiting factors in economic, social development, and the democratic process. Islamic law (sharia) strictly regulates the prohibition of all forms of betrayal of trust, bribery, and illegal taking of property, all of which are fundamental elements of corruption. To facilitate understanding in this writing, we use research methods including; by increasing the exploration of data sources from various literatures related to corruption from an Islamic perspective, so that we can draw the conclusion that Islam with its legal system offers an effective way to build a just, clean, and civilized society.